2007
DOI: 10.1302/0301-620x.89b9.18528
|View full text |Cite
|
Sign up to set email alerts
|

Early results for treatment of three- and four-part fractures of the proximal humerus using the PHILOS plate system

Abstract: Secure fixation of displaced proximal fractures of the humerus is a challenging problem. A total of 32 patients with acutely displaced three- or four-part proximal fractures of the humerus were treated by open reduction and internal fixation using the proximal humeral internal locking system (PHILOS) plate. There were 23 women and nine men with a mean age of 59.9 years (18 to 87). Data were collected prospectively and the outcomes were assessed using the Constant score. The mean follow-up was for 11 months (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
141
0
20

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(174 citation statements)
references
References 19 publications
(26 reference statements)
13
141
0
20
Order By: Relevance
“…15,16,17 In our study we utilized the deltopectoral approach in the patients of the proximal humerus fractures, the important points that must be taken care of are the placement of the plate of proper length, using the fluoroscopic imaging when placing the screws in the correct position and avoiding the varus displacement by ensuring support to the medial side of the cortex. 18,19,20 The overall complication rate in our study was found to be 18% and 10% of the patients had varus malunion, while the remainder of the complications were impingement, infection, failure of fixation and intra articular screw, revision surgeries were performed for the patients with deep infection and failure of fixation. In the study by Egol et al they had an infection rate of 1.61% in their case series and similar rate of observed in a study by Moonot et al and Gardner et al, in which the patients of infection were treated with antibiotics only.…”
Section: Discussionmentioning
confidence: 52%
“…15,16,17 In our study we utilized the deltopectoral approach in the patients of the proximal humerus fractures, the important points that must be taken care of are the placement of the plate of proper length, using the fluoroscopic imaging when placing the screws in the correct position and avoiding the varus displacement by ensuring support to the medial side of the cortex. 18,19,20 The overall complication rate in our study was found to be 18% and 10% of the patients had varus malunion, while the remainder of the complications were impingement, infection, failure of fixation and intra articular screw, revision surgeries were performed for the patients with deep infection and failure of fixation. In the study by Egol et al they had an infection rate of 1.61% in their case series and similar rate of observed in a study by Moonot et al and Gardner et al, in which the patients of infection were treated with antibiotics only.…”
Section: Discussionmentioning
confidence: 52%
“…Older age and requiring revision surgery were mentioned as the most predictive factors yielding undesirable outcome. Two other reports from early experiences by Moonot & Koukakis [9,10] have also provided valuable information with almost similar outcomes. In the study by Moonot, it was mentioned that good bone density permits early post-operative mobilization of upper extremity.…”
Section: Discussionmentioning
confidence: 77%
“…The Proximal Humeral Internal Locking System (Philos®) plate has specifically been designed to provide stability in proximal humeral fractures. It can be applied with a minimally invasive method and has screws which are placed in converging and diverging directions [9]. Several holes in the proximal part of the plate function as suturing anchors to the rotator cuff.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has similar results compared with other studies of surgical management of the proximal humerus. 25,[30][31][32][33][34][35][36] Proximal humerus fractures occur more commonly in the middle age group. Numerous age-related studies point toward this, and our study is consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%